Fluoroquinolone Versus Nonfluoroquinolone Treatment of Bloodstream Infections Caused by Chromosomally Mediated AmpC-Producing Enterobacteriaceae - Sarah Grace Gunter; Katie E. Barber; Jamie L. Wagner; Kayla R. Stover (MDPI AG, 2020)
Objectives: Chromosomally mediated AmpC-producing Enterobacteriaceae (CAE) display high susceptibility to fluoroquinolones; minimal clinical data exist supporting comparative clinical outcomes. The objective of this study was to compare treatment outcomes between fluoroquinolone and nonfluoroquinolone definitive therapy of bloodstream infections caused by CAE. Methods: This retrospective cohort assessed adult patients with positive blood cultures for CAE that received inpatient treatment for ≥48 h. The primary outcome was difference in clinical failure between patients who received fluoroquinolone (FQ) versus non-FQ treatment. Secondary endpoints included microbiological cure, infection-related length of stay, 90-day readmission, and all-cause inpatient mortality. Results: 56 patients were included in the study (31 (55%) received a FQ as definitive therapy; 25 (45%) received non-FQ). All non-FQ patients received a beta-lactam (BL). Clinical failure occurred in 10 (18%) patients, with 4 (13%) in the FQ group and 6 (24%) in the BL group (p = 0.315). Microbiological cure occurred in 55 (98%) patients. Median infection-related length of stay was 10 (6-20) days, with a significantly longer stay occurring in the BL group (p = 0.002). There was no statistical difference in 90-day readmissions between groups (7% FQ vs. 17% BL; p = 0.387); one patient expired. Conclusion: These results suggest that fluoroquinolones do not adversely impact clinical outcomes in patients with CAE. When alternatives to beta-lactam therapy are needed, fluoroquinolones may provide an effective option.